IDENTIFICATION OF ANEMONEFISHES (Amphiprioninae) AND THEIR SIMBIONT IN SPERMONDE ARCHIPELAGO, SOUTH SULAWESI - Inayah Yasir; Syafiuddin Syafiuddin; Sumarjito Sumarjito (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2010)
The study was conducted in June 2009 around the waters of Samalona, Barranglompo, Koedingareng Keke, Badi, Langkai and Kapoposang islands, representing four zones of Spermonde Archipelago of South Sulawesi. Seven species of anemonefish from two genera were found living symbiotically with 7 species of sea anemones. Those fishes were Amphiprion clarkii, A. melanopus, A. ocellaris, A. sandaracinos, A. perideraion, A. polymnus and Premnas biaculeatus. Three of these fishes were simbiotically found with one species of anemone (specific symbiont), and one species of fish was symbiotically found with five species of anemones.Keywords: Amphiprioninae, Spermonde Archipelago, anemone symbiont